Llama Llama Talent Show - Dewdney, Anna; Netflix (Firm) (New York : Penguin Young Readers, 2021)
Look out, world--Llama Llama is a TV star! The beloved character, made famous by Anna Dewdney's best-selling picture books, is the star of his own original series, now airing on Netflix. In this episode-based Penguin Young Reader, Llama Llama and his friends prepare acts for the school talent show, but Llama Llama doesn't know what act to perform!
Keywords: Llamas -- Juvenile fiction; Friendship in children -- Juvenile fiction; Talent shows -- Juvenile fiction; Llamas -- Fiction; Friendship -- Fiction; Talent shows -- Fiction